Characterization of mechanical damage in granite - Minh-Phong Luong; Mehrdad Emami (Fracture and Structural Integrity)
This paper aims to illustrate the use of infrared thermography as a non-destructive and non-contact technique to observe the phenomenological manifestation of damage in granite under unconfined compression. It allows records and observations in real time of heat patterns produced by the dissipation of energy generated by plasticity. The experimental results show that this technique, which couples mechanical and thermal energy, can be used for illustrating the onset of damage mechanism by stress concentration in weakness zones.